2015
DOI: 10.1007/s11060-015-1875-1
|View full text |Cite
|
Sign up to set email alerts
|

Current status of intratumoral therapy for glioblastoma

Abstract: With emerging drug delivery technologies becoming accessible, more options are expected to become available to patients with glioblastoma (GBM) in the near future. It is important for clinicians to be familiar with the underlying mechanisms and limitations of intratumoral drug delivery, and direction of recent research efforts. Tumor-adjacent brain is an extremely complex living matrix that creates challenges with normal tissue intertwining with tumor cells. For convection-enhanced delivery (CED), the role of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 46 publications
(54 reference statements)
0
27
0
Order By: Relevance
“…At present, CNTs do not efficiently cross the BBB 22 . However, advances in the use of catheter driven infusion strategies such as convection enhanced delivery (CED) 23 may allow for tumor specific delivery of CNTs. CED bypasses the BBB and relies on pressure-driven infusion through an intracranial catheter to distribute macromolecules along a pressure gradient rather than relying only on diffusion.…”
Section: Introductionmentioning
confidence: 99%
“…At present, CNTs do not efficiently cross the BBB 22 . However, advances in the use of catheter driven infusion strategies such as convection enhanced delivery (CED) 23 may allow for tumor specific delivery of CNTs. CED bypasses the BBB and relies on pressure-driven infusion through an intracranial catheter to distribute macromolecules along a pressure gradient rather than relying only on diffusion.…”
Section: Introductionmentioning
confidence: 99%
“…Backflow of infusate can be induced by tissue disruption, high infusion rates, and large catheter diameter [59]. The disappointing outcome of the PRECISE trial, which compared the efficacy of CED of citredekin besudotox with Gliadel® wafers, has been attributed to inadequate distribution likely due to suboptimal catheter placement [6062]. Considerable progress is being made in the area of catheter design, especially the development of multi-port catheters [7] and implantable systems that can be used for multiple infusions [63].…”
Section: Challenges With Convection-enhanced Deliverymentioning
confidence: 99%
“…Intracranial drug administration via CED may also potentially overcome systemic toxicities. In particular, catheter design and placement-in are critical components of any CED protocol (34). However, early studies may have been limited by "first generation" delivery techniques and recently reported improvements may potentially allow for better outcomes (26).…”
Section: Convection-enhanced Deliverymentioning
confidence: 99%